Factors Influencing Non-Performing Financing (NPF) at Sharia Banking - Jaenal Effendi; Usy Thiarany; Tita Nursyamsiah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
The risk of financing is the risk caused by the failure of the customers to fulfill their obligations. Non-performing financing (NPF) is a representation of financing risk that is channeled and has a direct impact on bank profitability. The value of NPF tends to increase annually with a value that is already close to the maximum limit set by Bank Indonesia of 5 percent. This condition is able to lead to the inefficiency of the banking system and in the long run, will have an impact on the sustainability of the bank. Therefore, the analysis of NPF factors should be conducted as a preventive measure and a risks controller of business activities. This research analyzes the factors influencing NPF at sharia banking (BUS) using a quarterly data from first quarter of 2012 until third quarter 2016. The method used in this research is panel data analysis. The result of analysis shows that the factors influencing NPF negatively and significantly are ratio of revenue sharing financing (RR), Return on Assets (ROA), inflation, Capital Adequacy Ratio (CAR) and Bank size while Gross Domestic Product (GDP) and Operating Cost to Operating Income (BOPO) have a significant positive effect.